Distribution and diversity of wildlife in northern Kenya in relation to livestock and permanent water points - Leeuw, Jan de; Waweru, M.N.; Okello, O.O.; Maloba, M.; Nguru, P.; Said, Mohammed Yahya; Aligula, H.M.; Heitkonig, I.M.; Reid, Robin S. (Elsevier, 2001)
Arid rangelands host a variety of drought-tolerant wildlife species, many of them requiring conservation efforts for the survival of their populations. The development of drinking water sources for people and livestock forms one of the main development interventions in these rangelands. However, the impact of availability of permanent drinking water on wildlife remains unknown. In this study we analyzed the distribution of wildlife and livestock in northern Kenya in relation to distance to permanent water. Livestock were concentrated in areas close to permanent water, while wildlife were frequently farther away from water; their distributions were inversely correlated. In addition, wildlife assemblages were more diverse farther from water. These results suggest that livestock and human activities related to water points negatively affect the distribution of wildlife